2021
DOI: 10.31661/gmj.v10i0.1931
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shockwave Therapy for Chronic Venous Ulcers: A Randomized Controlled Trial

Abstract: Background: Chronic venous ulcers (CVUs), demanding specialized care, are still a major socioeconomic problem facing health care systems worldwide. This study’s main goal was evaluating the efficacy of ESWT application as an AT in the treatment of wounds for curing CVUs. Materials and Methods: 50 patients presenting with CVUs were divided into two groups of ESWT and control randomly. Then, ESWT was applied one session per week, during four weeks, along with routine CB. The control group also received sham ESWT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This study found that treatment with ESWT was generally well tolerated. This observation is consistent with findings from other researchers [29,30]. This suggests the safety and acceptability of these treatments for patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found that treatment with ESWT was generally well tolerated. This observation is consistent with findings from other researchers [29,30]. This suggests the safety and acceptability of these treatments for patients.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that among the treated venous ulcers, 21 showed complete healing (49%), 7 showed significant improvement (16%), 12 improved (28%), and 3 did not improve (7%). In conclusion, the authors emphasized that EWST may advance the treatment of chronic venous leg ulcers [28][29][30].…”
Section: Discussionmentioning
confidence: 92%
“…Schaden et al [2] initiated the first trials on LI-ESWT for wound healing more than 10 yr later in 2007. In the meantime, several experimental and clinical studies documented accelerated tissue repair and regeneration in various wounds following ESWT [3] , [4] . However, the biomolecular mechanism by which this treatment modality exerts its therapeutic effects remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1 C). On the basis of promising results for low-intensity shockwave therapy (LI-ESWT) in the management of chronic ulcers [2] , [3] , [4] , we first used LI-ESWT in three cases of Fournier’s gangrene with secondary healing of skin flaps ( Fig. 1 D).…”
Section: Case Reportmentioning
confidence: 99%
“…The 12 studies [11][12][13][14][15][16][17][18][19][20][21][22] included a total of 573 participants. Individual sample sizes of identified trials ranged from 20 [11] to 106 [12].…”
Section: Sample Sizementioning
confidence: 99%